2002
DOI: 10.1074/jbc.m206065200
|View full text |Cite
|
Sign up to set email alerts
|

Human Testis/Sperm-specific Histone H2B (hTSH2B)

Abstract: Human sperm, unlike the sperm of other mammals, contain replacement histones with unknown biological functions. Here, we report the identification of the novel human gene coding for a testis/sperm-specific histone H2B (hTSH2B). This variant histone is 85% homologous to somatic H2B and has over 93% homology with the testis H2B of rodents. Using genomic PCR, two genetic alleles of hTSH2B were found in the human population. The hTSH2B gene is transcribed exclusively in testis, and the corresponding protein is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 45 publications
5
105
0
3
Order By: Relevance
“…The H2B variant documented in sea urchin has an N-terminal tail with a characteristic pentapeptide repeat that is highly charged [48,49]. Additional H2B variants have also been found in male gametic cells from lily [50] and, more recently, in bovine [51] and human spermatozoa [52], however, their specific roles remain to be elucidated.…”
Section: Histone H2bmentioning
confidence: 99%
“…The H2B variant documented in sea urchin has an N-terminal tail with a characteristic pentapeptide repeat that is highly charged [48,49]. Additional H2B variants have also been found in male gametic cells from lily [50] and, more recently, in bovine [51] and human spermatozoa [52], however, their specific roles remain to be elucidated.…”
Section: Histone H2bmentioning
confidence: 99%
“…Failure of H2A and H4 detection by N-terminal sequencing can be attributed to N-terminal acetylation reported in these latter histones (48 -50), which blocks the N-terminal sequencing procedure. PTderived histone sequences do not share any homology to mammalian testis-specific histone variants (51,52), although no bovine testis-specific histone variant has been characterized to date (53). Furthermore, 2D AUT/SDS-PAGE, and subsequent immunoblot analysis confirmed that these PT-derived histones are somatic-type, based on their identical characteristics to calf thymus core somatic histones.…”
Section: Figmentioning
confidence: 99%
“…This may reflect the intrinsic heterogeneity in the mature human sperm population. One of the possible reasons for such variation may be due to the sperm-specific histone TSH2B [31,32]. This histone is present in only a 30% subpopulation of sperm cells.…”
Section: Discussionmentioning
confidence: 99%